Pengaruh Keasaman Medium dan Imobilisasi Gugus Organik pada Karakter Silika Gel dari Abu Sekam Padi - Sriyanti, Sriyanti; Taslimah, Taslimah; Nuryono, Nuryono; Narsito, Narsito (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2005)
Silica gel is well known as a material that may be used as adsorbent, host matrix for catalyst, etc. Hence, synthesis of silica gel from rice hull ash has been done by evaluation of the effect of medium acidity and organic group immobilized in the snythesis of silica gel.Synthesis of silica gel was done by adding sodium silicate solution from rice hull ash to hydrochloric acid until pH 3, 5 and 7. Immobilization of thiol group and amino group in silica was done by adding 3-mercaptopropyltrimethoxysilane or 3-aminopropyl-trimethoxysilane to sodium silicate solution and hydrochloride acid solution until pH: 7. The products were characterized by X-ray deffractometer and FTIR Spectroscopy.Results showed that porousitas of silica increased with increasing medium acidity ( decreasing pH medium).Immobilization thiol or amino group in silica added a functional group on silica but did not destroy primary structure of silica gel.Key Words: Silica Gel, Rice Hull Ash, 3-mercaptopropyltrimethoxysilane, 3-aminopropyl-trimethoxysilane.